Against all odds: Tentative steps toward efficient information sharing in groups - Darius Schlangenotto; Wendelin Schnedler; Radovan Vadovič (Games, 2020)
When groups face difficult problems, the voices of experts may be lost in the noise of others' contributions. We present results from a "naturally noisy" setting, a large first-year undergraduate class, in which the expert's voice was "lost" to such a degree that bringing forward even more inferior information was optimal. A single individual had little chance to improve the outcome and coordinating with the whole group was impossible. In this setting, we examined the change in behavior before and after people could talk to their neighbors. We found that the number of people who reduced noise by holding back their information strongly and significantly increased.
Keywords: D71; D72; D81; D82; C99; 330; communication; coordination; information aggregation; swing voter's curse